Effectiveness of artificial diet enriched by spinach extract on molting stimulation to produce soft shell crab - Aslamyah, Siti; Fujaya, Yushinta (Indonesian Society of Scientific Aquaculture (ISSA), 2011)
Artificial feed is an alternative media applications spinach extract (EB) that is known to contain molting stimulant. However, utilization of the artificial feed is related to its expensive cost, with a very high protein concentration since it's mainly produced from fish based materials, so need to be studied artificial feed formulation with substitution of vegetable material in stimulating molting and growth of mud crabs. Four formula artificial feed enriched EB (700 ng/g crab) used in this study were feed A (fish, crab shells, and cassava), feed B (fish, silage, shell crab, and cassava), feed C (fish, silage, shell crab, soy flour, and cassava), and feed D (fish, silage, shell crab, soy flour, corn starch, and pollard), trash fish and feed A without EB as control. During the test, mud crab intermolt phase was culture individually in crab box placed in pond. The results showed that the percentage of molting and weight growth in their respective in the feed A (44% and 41.96%); feed B (56% and 31.57%); feed C (74% and 23.20%); feed D (50% and 39.15%); trash feed control (24% and 50.66%); and feed A without EB (28% and 35.11%). An opposite phenomenon, where the feed C with the highest percentage of molting but with the lowest growth rate, the opposite occurs in the control of trash feed. This is apparently the effect of spinach extract as a stimulant molting, where performance can be optimized with a complete and balance nutrient composition. This prediction is supported by the analysis of protein content of crabs tested at the highest feed C treatment compared with the control feed. Key words: spinach extract, soft shell crab, molting, artificial feed, growth ABSTRAK Pakan buatan merupakan alternatif media aplikasi ekstrak bayam (EB) yang diketahui mengandung stimulan molting. Namun demikian, pakan buatan yang digunakan masih mahal dengan kandungan protein yang tinggi, karena berbahan dasar ikan, sehingga perlu dikaji formulasi pakan buatan dengan subtitusi berbagai bahan nabati dalam menstimulasi molting dan pertumbuhan kepiting bakau. Empat formula pakan buatan yang diperkaya EB (700 ng/g kepiting) digunakan pada penelitan ini, yaitu Pakan A (ikan, cangkang kepiting, dan ubi), Pakan B (ikan, silase, cangkang kepiting, dan ubi), Pakan C (ikan, silase, cangkang kepiting, tepung kedelai, dan ubi), dan Pakan D (ikan, silase, cangkang kepiting, tepung kedelai, tepung jagung, dan pollard). Pakan rucah dan pakan A tanpa EB digunakan sebagai kontrol. Selama penelitian, kepiting bakau fase intermolt dipelihara secara individu dalam crab box yang diletakkan di tambak. Hasil penelitian menunjukkan persentase molting dan pertumbuhan bobot masing-masing pada Pakan A (44% dan 41,96%); Pakan B (56% dan 31,57%); Pakan C (74% dan 23,20%); Pakan D (50% dan 39,15%); kontrol pakan rucah (24% dan 50,66%); dan pakan A tanpa EB (28% dan 35,11%). Terjadi anomali, yaitu Pakan C dengan persentase molting tertinggi, tetapi dengan tingkat pertumbuhan terendah, namun terjadi sebaliknya pada kontrol pakan rucah. Hal ini diduga efek dari ekstrak bayam sebagai stimulan molting, dimana kinerjanya dapat dioptimumkan dengan komposisi nutrien lengkap dan seimbang. Pendugaan ini didukung hasil analisis kadar protein kepiting uji pada perlakuan Pakan C tertinggi dibandingkan kontrol. Kata kunci: Ekstrak bayam, kepiting cangkang lunak, molting, pakan buatan, pertumbuhan